Gender equality and development - World Bank (Washington, DC : World Bank, 2011)
The World Development Report 2012: Gender Equality and Development argues that gender equality is a core development objective in its own right. It is also smart economics. Greater gender equality can enhance productivity, improve development outcomes for the next generation, and make institutions more representative. The Report also focuses on four priority areas for policy going forward: (i) reducing excess female mortality and closing education gaps where they remain, (ii) improving access to economic opportunities for women (iii) increasing women's voice and agency in the household and in society and (iv) limiting the reproduction of gender inequality across generations
1. Taking stock of gender equality -- 2. What has driven progress? What impedes it -- 3. The role of and potential for public action
Includes bibliographical references and index
Keywords: Equality; Women in development; Women's rights; Women -- Developing countries